Body Adiposity Partially Mediates the Association between FTO rs9939609 and Lower Adiponectin Levels in Chilean Children - Carolina Ochoa-Rosales; Lorena Mardones; Marcelo Villagrán; Claudio Aguayo; Miquel Martorell; Carlos Celis-Morales; Natalia Ulloa (MDPI AG, 2023)
Children carrying the minor allele 'A' at the fat mass and obesity-associated protein (FTO) gene have higher obesity prevalence. We examined the link between FTO rs9939609 polymorphism and plasma adiponectin and the mediating role of body adiposity, in a cross-sectional study comprising 323 children aged 6-11 years. Adiponectin and FTO genotypes were assessed using a commercial kit and a real-time polymerase chain reaction with high-resolution melting analysis, respectively. Body adiposity included body mass index z-score, body fat percentage and waist-to-hip ratio. To investigate adiponectin (outcome) associations with FTO and adiposity, linear regressions were implemented in additive models and across genotype categories, adjusting for sex, age and Tanner's stage. Using mediation analysis, we determined the proportion of the association adiponectin-FTO mediated by body adiposity. Lower adiponectin concentrations were associated with one additional risk allele (βadditive = −0.075 log-μg/mL [−0.124; −0.025]), a homozygous risk genotype (βAA/TT = −0.150 [−0.253; −0.048]) and a higher body mass index z-score (β = −0.130 [−0.176; −0.085]). Similar results were obtained for body fat percentage and waist-to-hip ratio. Body adiposity may mediate up to 29.8% of the FTO-adiponectin association. In conclusion, FTO rs9939609-related differences in body adiposity may partially explain lower adiponectin concentrations. Further studies need to disentangle the biological pathways independent from body adiposity.